Gold nanoantennas on a pedestal for plasmonic enhancement in the infrared - Huck, Christian; Neubrech, Frank; Vogt, Jochen; Pucci, Annemarie (ACS photonics, 2015)
The coupling of an infrared plasmon-polariton excitation of a metal nanoparticle to a vibrational excitation of a similar energy enables strong vibrational signal enhancement. However, the commonly used planar substrates substantially weaken plasmonic resonances because of their polarizability, and, furthermore, a great part of the enhanced near-field is inside the substrate and thus not available for an analyte. In this contribution we report on a way to reduce these undesirable influences of the substrate by fabricating gold nanowires on high pedestals and thus in reduced contact with the substrate. The influence of the height of the pedestal is an important parameter for the plasmonic near-field enhancement, as we show with finite-difference time-domain simulations. Comparing the plasmonic response and the SEIRA activity of the rods prepared by standard electron beam lithography and the rods additionally treated with reactive ion etching to remove the silicon substrate at the hot-spots of the rods reveals not only the change of the plasmonic-resonance spectrum but also interesting differences of the enhanced phonon-polariton signal from the silicon dioxide layer on the silicon substrate and the about 1 order of magnitude stronger vibrational signal enhancement for an adsorbate monolayer.
Gesehen am 02.06.2020